A Portrait of Global Value Chain Linkages of Indian Manufacturing. Issue 2 (September 2021) - Reddy, Ketan; Sasidharan, Subash
This article provides an overview of India's participation in global value chains (GVCs). Using multiple databases at the aggregate and industry levels, this article documents the trends in GVC participation of India during the last three decades. Authors further differentiate between India's backward and forward integration at the country level before evaluating the industry-specific dynamics of GVCs in India. In this study, authors also shed light upon the rising servicification of Indian manufacturing, and highlight the importance of services' value addition in promoting GVC integration of India. JEL Codes: F1, F15, D57